(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, the purpose of teaching the subject of primary preparation before convocation is the methodology of developing the professional training of future teachers based on the technological approach, as well as the quality of the subject of primary preparation before convocation, its educational significance, the training leader’s military and the level of pedagogical knowledge, his spiritual maturity and methodical skills are mentioned